THE EFFECTIVENESS OF CHATGPT TO IMPROVE THE STUDENTS' WRITING SKILLS (STUDY AT STUDENTS OF ENGLISH DEPARTMENT UNIVERSITAS MUSLIM INDONESIA) (Karya Ilmiah Mahasiswa (KIMA), 2026)
AbstractThis research aimed to determine whether students could effectively use ChatGPT to improve the quality of their writing skills and the key factors that influenced the effectiveness of using ChatGPT in improving writing skills. This study evaluated ChatGPT's effectiveness in supporting the writing skills of fourth-semester students in the English Education Study Program at Universitas Muslim Indonesia through a quantitative survey. The results of the research showed that ChatGPT improved the quality of students' writing, particularly in idea development, sentence structure, and confidence, through constructive feedback. Students felt supported by ChatGPT's suggestions and examples, which helped them develop ideas more effectively and expand their vocabulary. The study demonstrated that ChatGPT was an effective tool for writing instruction, significantly enhancing students' learning outcomes. Integrating ChatGPT into writing education had important implications for future educational development.